2020
DOI: 10.1007/s10389-020-01304-0
|View full text |Cite
|
Sign up to set email alerts
|

Depression, sleeping pattern, and suicidal ideation among medical students in Bangladesh: a cross-sectional pilot study

Abstract: Background Depression is a major morbidity and the most common mental disorder among the medical students in medical schools globally. Undergraduate students suffer stress more due to their academic curriculum than the students of other faculties. In low-resource settings like Bangladesh, there is a dearth in research on the mental health of undergraduate medical students. This pilot study was conducted to add to the existing limited evidence by reporting the prevalence of depression and describing sleeping pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
26
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 25 publications
5
26
2
Order By: Relevance
“…The prevalence of depressive symptoms was found to be consistent with the previous studies in Bangladesh among university students [ 16 ], job-seeking graduate students [ 43 ] and medical students [ 27 , 44 ]. But the prevalence of depression in this study is lower than the finding from a study among Bangladeshi first-year university students that used the PHQ-9 scale to assess the level of depression [ 15 ].…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The prevalence of depressive symptoms was found to be consistent with the previous studies in Bangladesh among university students [ 16 ], job-seeking graduate students [ 43 ] and medical students [ 27 , 44 ]. But the prevalence of depression in this study is lower than the finding from a study among Bangladeshi first-year university students that used the PHQ-9 scale to assess the level of depression [ 15 ].…”
Section: Discussionsupporting
confidence: 88%
“…The present study obtained a significant association concerning (i) short sleep time and depressive symptoms (ii) low physical activity and depressive symptoms. This compares with recent Bangladeshi studies [ 15 , 16 , 27 ] who reported that students engaged in lower physical activity and having poor sleeping habit were more likely to be depressed than those engaging in regular physical exercise and having normal total sleep time. .…”
Section: Discussioncontrasting
confidence: 60%
See 1 more Smart Citation
“…Globally, medical and dental schooling is perceived as a highly stressful education, where students face a higher level of stress, anxiety, and depression compared to peers studying other subjects [ 9 , 10 , 11 ]. In particular, research shows that dental students are prone to higher burnouts compared to medical students as it involves patient interaction during both theoretical and clinical course elements [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…While one study revealed the cumulative depression rate was 39%, another one found 81% only among 1st year students. 4,5 So, more studies need to be undertaken to determine the prevalence and identify the responsible factors so that students can be quickly screened, assessed and dealt accordingly to avoid short and long term consequences.…”
Section: Introductionmentioning
confidence: 99%